Pectinase production by Aspergillus niger using banana (Musa balbisiana) peel as substrate and its effect on clarification of banana juice - Barman, Sumi (J Food Sci Technol, 2014)
Optimization of substrate concentration, time of incubation and temperature for crude pectinase production from A. niger was carried out using Bhimkol banana (Musa balbisiana) peel as substrate. The crude pectinase produced was partially purified using ethanol and effectiveness of crude and partially purified pectinase was studied for banana juice clarification. The optimum substrate concentration, incubation time and temperature of incubation were 8.07 %, 65.82 h and 32.37 °C respectively, and the polygalacturonase (PG) activity achieved was 6.6 U/ml for crude pectinase. The partially purified enzyme showed more than 3 times of polygalacturonase activity as compared to the crude enzyme. The SDS-PAGE profile showed that the molecular weight of proteins present in the different pectinases varied from 34 to 42 kDa. The study further revealed that highest clarification was achieved when raw banana juice was incubated for 60 min with 2 % concentration of partially purified pectinase and the absorbance obtained was 0.10.